2015
DOI: 10.6018/analesps.31.3.179151
|View full text |Cite
|
Sign up to set email alerts
|

Ciberbullying en adolescentes y jóvenes del País Vasco: Cambios con la edad

Abstract: Resumen: El estudio tuvo como objetivo analizar cambios con la edad en ciberbullying. La muestra fue de 3026 participantes del País Vasco de 12 a 18 años. Se administró el Test Cyberbullying para evaluar la frecuencia con la que 15 conductas han sido sufridas, realizadas y observadas durante el úl-timo año, y permite obtener 4 indicadores psicométricos: victimización, agresión, observación, victimización-agresiva. Los resultados evidenciaron: 1) Similar porcentaje de víctimas de 12 a 18 años en las 15 conducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
4
61

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 23 publications
3
17
4
61
Order By: Relevance
“…Even so, it is noted that the mean on the cybervictimization scale increases as age advances -according to the age groups of 11-13, 14-15 and 16-18. Unlike Garaigordobil (2015), who did not find differences in age on this scale, significant differences were found. In contrast to the data commonly obtained in traditional bullying, more cyberbullying cases were found in the upper grades, as occurs in other studies (Barboza, 2015;Cappadocia et al, 2013;Kowalski & Limber, 2007).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Even so, it is noted that the mean on the cybervictimization scale increases as age advances -according to the age groups of 11-13, 14-15 and 16-18. Unlike Garaigordobil (2015), who did not find differences in age on this scale, significant differences were found. In contrast to the data commonly obtained in traditional bullying, more cyberbullying cases were found in the upper grades, as occurs in other studies (Barboza, 2015;Cappadocia et al, 2013;Kowalski & Limber, 2007).…”
Section: Discussionmentioning
confidence: 49%
“…In spite of this, there is also no consistency in the differences that the different authors have found. We find some papers where no significant statistical differences are reported (Garaigordobil, 2015;Pelfrey & Weber, 2013;Stewart et al, 2014;Waasdorp & Bradshaw, 2015). There are also studies where those involved, as cybervictims, were the oldest of the sample (Jung et al, 2014;Walrave & Heirman, 2011).…”
Section: Differences In Age or Academic Yearmentioning
confidence: 98%
“…Esse dado reforça a tendência apontada em alguns estudos, que indicam maior envolvimento de meninas em cyber agressão (Beckman et al, 2013;Calvete et al, 2015), embora ainda não exista um consenso na literatura em relação a esse aspecto (Slonje, Smith, & Frisén, 2013). Por sua vez, o maior envolvimento dos adolescentes mais velhos no cyberbullying também vai ao encontro da literatura (Tarapdar & Kellett, 2013) embora também para esses casos os resultados variem conforme os instrumentos utilizados e o intervalo de tempo considerado (Garaigordobil, 2015).…”
Section: Análise De Dadosunclassified
“…Así como también se requiere mejorar la organización de los centros educativos, implementado acciones relacionadas con el uso saludable de las TIC en su Plan de Convivencia de Centro y confeccionando protocolos de actuación para situaciones de cualquier tipo de violencia entre el alumnado a través de Internet. Ya que como señala Garaigordobil (2015) aunque en los últimos años ha aumentado considerablemente la sensibilización sobre la importancia de trabajar la (ciber)convivencia en los centros escolares, la aplicación sistemática de programas específicos sobre esta temática sigue siendo una de nuestras asignaturas pendiente.…”
Section: Discusión Y Conclusionesunclassified